2013
DOI: 10.1007/s00280-013-2307-6
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of erlotinib in patients with advanced non-small-cell lung cancer harboring epidermal growth factor receptor mutations: additive analysis of pharmacokinetics

Abstract: Background We conducted a phase II trial of erlotinib in patients with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Including this result, some reports indicated that a high ratio of the late (reaching a steady-state level of gefitinib) and early (after the first or second administrations) plasma trough levels of EGFR-TKIs predicts their antitumor activity [5,8]. As mentioned above, this high ratio might reflect the change in the t 1/2 of EGFR-TKIs in the early treatment phase.…”
Section: Discussionmentioning
confidence: 80%
“…Including this result, some reports indicated that a high ratio of the late (reaching a steady-state level of gefitinib) and early (after the first or second administrations) plasma trough levels of EGFR-TKIs predicts their antitumor activity [5,8]. As mentioned above, this high ratio might reflect the change in the t 1/2 of EGFR-TKIs in the early treatment phase.…”
Section: Discussionmentioning
confidence: 80%
“…We next examined growth-inhibitory effects of erlotinib and PS, alone and in combination. NSCLC patients usually receive a daily dose of 150 mg erlotinib, which results in plasma levels between 1 and 3 μM [ 27 ]. Thus we chose to treat the EGFR wildtype cells with an erlotinib concentration of 2 μM.…”
Section: Resultsmentioning
confidence: 99%
“…A direct relationship between exposure to erlotinib and observed clinical response must be proven [65]. Some authors describe a statistically significant correlation between exposure and efficacy [66,67], while others only point to a non-statistically significant trend or relationship between both parameters [68,69]. The preclinical study carried out by Hidalgo et al [61] suggested that a target C trough greater than 500 mg/L in humans would be adequate for the inhibition of EGFR receptors, so this target concentration was adopted for later studies.…”
Section: Erlotinibmentioning
confidence: 99%